Effectiveness of State-Based Relaxation Therapy on Externalizing/Internalizing Problems in Students with Intermittent Explosive Disorder - Rava, Nazanin; Jahan, Faezeh; Sabahi, Parviz; Peyvandi, Golnaz (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The aim of this study was to investigate the effectiveness of state-based relaxation therapy on externalizing/internalizing problems in students with Intermittent Explosive Disorder (IED). Methods and Materials: The research method was a quasi-experimental design with a pretest-posttest and follow-up with a control group. The statistical population included all adolescents aged 12-18 years with IED in the 2023-2024 academic year, who were studying in schools in Tehran. The sample size consisted of 30 individuals (15 in the experimental group and 15 in the control group) selected from the statistical population using convenience sampling and assigned to experimental and control groups. The experimental group received state-based relaxation therapy, while the control group remained on the waiting list. The research instruments included the Intermittent Explosive Disorder Questionnaire (Coccaro et al., 2017) and the Achenbach Emotional and Behavioral Problems Questionnaire (Achenbach & Rescorla, 2003). Data were analyzed using repeated measures analysis of variance (ANOVA) and SPSS-27 software. Findings: The results indicated that state-based relaxation therapy had a significant effect on externalizing/internalizing problems in the posttest and follow-up stages. Conclusion: The findings of this study provide useful information regarding state-based relaxation therapy, and psychologists and psychiatrists can use this intervention to improve externalizing/internalizing problems in students with IED.